TINGKAT KEPUASAN MAHASISWA TERHADAP KINERJA PELAYANAN AKADEMIK SEKOLAH TINGGI ILMU EKONOMI NASIONAL INDONESIA (STIENI) JAKARTA - Siagian, Gary Yefa Herbeth (Jurnal Ecoment Global, 2020)
This research is aimed at finding out about the characteristics  and level of the students’ satisfaction with the academic service performance at the Indonesian National School of Economics (Sekolah Tinggi Ilmu Ekonomi Nasional Indonesia  (STIENI]), Jakarta. This research has applied the methods of surveying and of quata sampling to 100 respondents. The analytical data has used descriptive analysis, the Method of Important Performance Analysis (MIPA), and the Customer Satisfaction Index (CSI). The results hereof indicate the respondents’ characteristics that the majority, 70%, of the STIENI students are female. As to their age, the majority, 80%, are > 25 years.  The semester/ grade in this research is the third (3rd),  being 40% in number. The study program, 70%, is management. Concerning the students’ status, 75% of them are employees’ class. As to the frequency of visits, the majority of STIENI students are >3 times or 70% relative to lecturing needs. The students’ level of satisfaction with the academic service performance provided by the STIENI campus is 0.60 based on the criterion of being content. It means that the academic service performance of STIENI campus has lived up to the students’ expectations. Keyword : Satisfaction level, Servis Performance, Academic, Students